(untitled) (Al-Academy, 2019)
The theatrical show consists of theatrical techniques that form the space to display the play that may form conscious visual effects about the receiver. The current search included the (Research problem) which is the immediate question ((What makes the theatrical techniques dazzling and visually exciting in a certain theatrical show?))It also included (the importance of research) by highlighting the importance of theatrical techniques and the mechanism of contrast.It also identified the visual stimulus of theatrical techniques in the theater show. It also included the (research limits), which were temporally determined by the period (1990-1998) and spatially, the Iraqi theater shows (Baghdad), in which theatrical techniques constituted visual, philosophical and aesthetic excitement. Objectively, I chose to study the stimuli caused by theatrical techniques in the theatrical show.The (theoretical framework) included two sections, the first of which is concerned with the study of directorial methods and their importance in detailing technical stimuli.The second section dealt with the technical stimulus and performing it in the Arab - Iraqi theater. The chapter concluded with indicators that resulted from the theoretical framework.The research procedures included the research community and samples chosen intentionally based on the indicators resulting from the theoretical framework as a tool for analysis within the descriptive analytical method and viewing the shows and the photographs then comes the analysis of the two selected shows (Isolation in the Crystal) (in the Heights of Love)